Social Media Marketing Strategy Strategic Content Capability and Social Engagement: A Pathway to Social Media Performance in Indonesian MSMEs - Pratama, Putra; Najmudin, Najmudin; Sudarto, Sudarto; Novandri, Weni; Pradipta Setyanto, Refius; Rabiatul Adawiyah, Wiwiek (The Es Economics and Entrepreneurship, 2025)
The tremendous development of social media usage—which now exceeds 5.4 billion people worldwide—has brought digital platforms to the center of marketing strategy. However, existing research frequently ignores the impact of strategic planning and internal content skills on engagement and performance. By investigating the impact of Digital Content Capability (DCC) and Social Media Marketing Strategy (SMMS) on Customer Engagement (CE) and Social Media Performance (SMP) among Indonesian fashion MSMEs, this study fills a significant knowledge gap. Data from 130 respondents were evaluated quantitatively using Structural Equation Modeling (SEM-PLS). The results suggest that DCC and SMMS have a considerable impact on CE, which then mediates their effect on SMP. The findings show that social media efficacy is based on more than just frequency or platform choice, but also on the strategic capacity to create relevant, consistent, and analytically driven content. This study provides both theoretical insights and practical methods for SMEs to improve their content strategies and digital outcomes.